Performance indicators in breast cancer screening in the European Union: A comparison across countries of screen positivity and detection rates. Issue 7 (23rd March 2020) - Armaroli, Paola; Riggi, Emilia; Basu, Partha; Anttila, Ahti; Ponti, Antonio; Carvalho, Andre L.; Dillner, Joakim; Elfström, Miriam K.; Giordano, Livia; Lönnberg, Stefan; Ronco, Gugliemo; Senore, Carlo; et al.
Abstract : Comparable performance indicators for breast cancer screening in the European Union (EU) have not been previously reported. We estimated adjusted breast cancer screening positivity rate (PR) and detection rates (DR) to investigate variation across EU countries. For the age 50–69 years, the adjusted EU‐pooled PR for initial screening was 8.9% (cross‐programme variation range 3.2–19.5%) while DR of invasive cancers was 5.3/1, 000 (range 3.8–7.4/1, 000) and DR of ductal carcinoma in situ (DCIS) was 1.3/1, 000 (range 0.7–2.7/1, 000). For subsequent screening, the adjusted EU‐pooled PR was 3.6% (range 1.4–8.4%), the DR was 4.0/1, 000 (range 2.2–5.8/1, 000) and 0.8/1, 000 (range 0.5–1.3/1, 000) for invasive and DCIS, respectively. Adjusted performance indicators showed remarkable heterogeneity, likely due to different background breast cancer risk and awareness between target populations, and also different screening protocols and organisation. Periodic reporting of the screening indicators permits comparison and evaluation of the screening activities between and within countries aiming to improve the quality and the outcomes of screening programmes. Cancer Screening Registries would be a milestone in this direction and EU Screening Reports provide a fundamental contribution to building them. Abstract : What's new? Approximately half a million women in the European Union (EU) are afflicted with breast cancer but the screening process is not standardized across Europe. Here, the authors used data from the Second EU Screening Report to present adjusted breast cancer screening positivity and detection rates across Europe. They find large variability by country in detection rates, likely due to differences in background risk, awareness of the target populations, and different screening protocols, underscoring the need for periodic reporting of performance indicators in EU‐Member States.